The characteristics of several varieties and the effect of cropping management design on the level of pest damage and seed yield of soybeans in rainfed lowland rice fields - Fattah, Abdul; Hannan, Muhammad Fitrah Irawan; Yasin, M.; Harnowo, Didik; Nugraha, Yudhistira; Wulanningtyas, Heppy Suci; Najamuddin, Erwin; Saenong, Sudjak; Rahman, Ayyub Ar; Winanda, Elisa; Hasanuddin, Rahmi; Rohimatun,; et al. (Frontiers in Sustainable Food Systems, 2024)
Design of cropping method and type of variety are one of the most important factors in increasing soybean productivity and the level of pest attack and predator populations. This study aims to determine the most effective planting method and variety types in an effort to increase soybean productivity in rainfed lowland areas in South Sulawesi, Indonesia. The design used in this study was the split plot design, and the varieties (PU) used were as follows: (1) Detap-1, (2) Devon-1, and (3) Derap-1. However, the subplot (AP) was a planting method and three replicates: (1) farmer’s transplanting method (transplanting row: 20 cm × 20 cm), (2) method of transplanting double rows, and (3) method of transplanting three rows. The results showed that the highest number of branchesper plant was observed in the Legowo three planting method with the Detap-1 variety. The lowest level of leaf damage due to Spodoptera litura attack was observed in the Legowo double rows planting method with the Devon-1 variety (11.07%), and the highest level of leaf damage was observed in the jajar horn planting method (farmer’s method) with the Derap-1 variety (16.47%). The level of pod damage due to Etiella zinckenella attack was the lowest on Legowo three planting method on the Derap-1 variety (9.47%) and the highest on the Legowo double rows planting method on the Detap-1 variety (14.26%). The level of pod damage due to attack by pod-sucking pest Riptortus linearis was the lowest on Legowo three planting method on the (Derap-1) variety (8.02%) and the highest on the pod-sucking pest Riptortus linearis on the Devon-1 variety (13.43%). The length of the trichomes on soybean leaves was the highest on the Devon-1 variety (30.93%) and the lowest on Derap-1 (24.81). The highest number of trichomes on soybean leaves was on the Derap-1variety (57.67) and the lowest on the Devon-1 variety (32.20). The highest length of trichomes was on soybean pods on Detap-1 (29.11) and the lowest on Devon-1 (26.52), while the highest number of trichomes in soybean pods was on Devon-1 (222.47) and the lowest on Derap-1 (148.40). The highest seed yield was observed in Legowo three panting method with Derap-1 and Devon-1 varieties (2.02–2.08 t ha−1).